“Gestión comercial y su incidencia en las ventas de los pequeños productores de licor artesanal del cantón La Maná, periodo 2019 – 2020”. plan de capacitación. - Abrigo Vivas, Oscar Javier (2021)
The development project "Commercial Management and its impact on the sales of small producers of artisanal liquor in the Cantón La Maná, period 2019-2020". Training Plan, aims to evaluate the Commercial Management and its impact on the sales of small producers of artisanal liquor of the canton La Maná, period 2019 - 2020? The applied methodology was carried out through field research with interviews and surveys to the small producers and different consumer populations in the areas, where the lack of technology could be perceived, and a limited sales process with influencing factors such as sanitary registration, adequate packaging and very low sales values that reach $ 2 per liter of artisanal liquor for The hard work that is carried out at the time of extracting the artisanal liquor, it is determined to execute a training plan so that the micro-producers can innovate the production and commercialization process and establish cooperation ties between them to develop a brand at the national level, because the product is accepted and recognized; but limited knowledge is perceived in the process of elaboration and innovation in the sale of artisanal liquor in the localities. . Keywords: management, liquor, process, sales, product, commercial.